Human stress cardiomyopathy mimicking acute myocardial syndrome. Issue 5 (1st November 1997) - Pavin, D; Le Breton, H; Daubert, C
Abstract : Two cases of transient acute cardiomyopathy occurring in the immediate aftermath of intense emotional stress and without any identified aetiology are described. These two case reports, mimicking cases of acute cardiomyopathy described in patients with pheochromocytoma, suggest the possibility in man of acute catecholamine induced cardiomyopathy related to major emotional stress alone, a phenomenon so far reported only in animal experimental models.